Combatting mucosal melanoma: recent advances and future perspectives. (8th October 2018) - Tyrrell, Helen; Payne, Miranda
Mucosal melanomas are a rare subtype of melanoma and are associated with a particularly poor prognosis. Due to the rarity of the diagnosis, and the pace with which the management of cutaneous melanoma has evolved over recent years, there is little good evidence to guide management and evidence-based clinical guidelines are still in development in the UK. In this review we provide an overview of the management of mucosal melanoma, highlighting the critical differences between cutaneous and mucosal melanomas, before examining recent advances in the systemic treatment of this disease and likely future directions.